Reasons behind decreasing trends in caesarean section (CS) rates – royal Bolton hospital (RBH). (18th April 2012) - Bardapure, J; Tomlinson, AJ; Moss, R; Katakam, N
Abstract : Introduction: Reasons for rising CS rates in the UK include rising maternal age at first pregnancy, improved safety of the procedure, changes in women's preferences and growing proportion of women with a previous CS. Objective: Review the reasons for decreasing CS trends at RBH whilst rising CS rates nationally. National annual CS rates from 2007- 2010 are 24.3%, 24.6%, 24.6%, 24.8% respectively while corresponding CS rates at RBH are 23.3%, 23.4%, 21.8%, 21.4% and 22.8 % (till Sept'11). Material and methods: Retrospective computerised database review of CS rates was done from Jan'07-Sept'11 and subdivided according to Robson's criteria. Significant changes in practice at RBH included introduction of 'Consultant of the week' (COW) system from October'08 and use of Propess® for induction of labour (IOL) from June'09. Results: (All singleton-term-cephalic) (Spontaneous labour –SL) Conclusions: Adoption of COW system and Propess have initially led to significant reduction in CS rate in multiparae in both SL and IOL group and in primiparae in SL (term, cephalic). Greater encouragement for vaginal birth in women with previous CS and review of reasons for CS in primiparae with IOL is recommended to understand the initial fall in CS rate followed by the rise.